Reference gene selection for real‐time quantitative PCR assays in different tissues of Huperzia serrata based on full‐length transcriptome sequencing. (24th November 2021) - Fu, Yanping; Niu, Fei; Jia, Hui; Wang, Yanli; Guo, Bin; Wei, Yahui
Abstract: Huperzia serrata ( H. serrata ) produces various types of effective lycopodium alkaloids, especially Huperzine A (HupA), which is a promising drug for the treatment of Alzheimer's disease. Numerous studies focused on the chemistry, bioactivities, toxicology, and clinical trials of HupA; however, the public genomic and transcriptomic resources are very limited for H. serrata research, especially for the selection of optimum reference genes. Based on the full‐length transcriptome datasets and previous studies, 10 traditional and three new candidate reference genes were selected in different tissue of H. serrata . Then, two optimal reference genes GAPDHB and HisH2A were confirmed by four analysis methods. In order to further verify the accuracy of the two reference genes, they were used to analyze the expression patterns of four HupA‐biosynthetic genes (lysine decarboxylas, RS‐norcoclaurine 6‐O‐methyltransferase, cytochrome P45072A1, and copper amine oxidase). The data suggested that the expression pattern of HupA‐biosynthetic genes was consistent with them in transcriptome sequencing in different tissue of H. serrata . This study identified that GAPDHB and HisH2A provides the reliable normalization for analyzing the HupA biosynthetic gene expression in different tissues of H. serrata on the transcriptional level.